"Force Fields" of Motherhood and Maternal Empowerment: An Indigenous Mother in Canada Engages the Narratives of African Caribbean Mothers in Barbados - Downe, Pamela (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
Isabel is a grandmother from a northern Cree community in Saskatchewan. As she copes with temporarily losing custody of her young grandson, she engages with the stories of two mothers from the eastern Caribbean, one who lives a similar life to hers and one from over two hundred years ago. This article presents that narrative engagement and argues that it constitutes a force field of maternal affinity that allows Isabel to recollect her own grandmother’s strength and perseverance. This kind of maternal affinity—extending across geographical distance, cultural divides, and historical periods—can be a source for maternal empowerment in three ways. First, it establishes a motherline that is significant in times of distress. Second, it gives rise to redemptive narratives that help mothers living with HIV and addiction navigate and mitigate the intruding forces of marginalization and disruption. Third, it creates a sense of longevity and safety that can be a much needed reprieve from the oppressive surveillance and scrutiny that Indigenous mothers in Canada face.